PENGARUH TECHNOLOGY READINESS ACCEPTANCE MODEL TERHADAP MINAT PENGGUNAAN BSI MOBILE (STUDI BSI KCP SAMARINDA BUNG TOMO) - Erika Wana Maharani Zein; Dedy Mainata; Arista Wibowo (Department of Islamic Banking, Faculty of Islamic Economics and Business (FEBI), State Islamic University of Sultan Aji Muhammad Idris Samarinda, 2026)
The research is motivated by the increasingly sophisticated technology, particularly in mobile banking, can be utilized by the Islamic banking industry as a service facility to assist customers with busy businesses or activities, providing effective and time-efficient service. This study aims to determine the Technology Readiness Acceptance Model on BSI Mobile usage intention among BSI Samarinda Bung Tomo Branch customers. The population in this study is BSI Samarinda Bung Tomo customer. This study uses a sampling technique with purposive sampling. The purpose of this research is to analyze the influence of Technology Readiness factors (optimism, innovativeness, discomfort, and insecurity) on TAM components (perceived usefulness and perceived ease of use) in influencing the intention to use BSI Mobile. This research adopts a quantitative method with a survey approach involving 120 respondents selected through convenience sampling. Data were analyzed using SmartPLS. The findings reveal that seven hypotheses were accepted: the influence of innovativeness, discomfort, and insecurity on perceived ease of use; the influence of perceived ease of use on perceived usefulness and intention to use; and the influence of perceived usefulness on intention to use. However, hypotheses concerning the effect of optimism on perceived ease of use, as well as innovativeness, discomfort, and insecurity on perceived usefulness, were rejected. These findings provide valuable insights for the development of BSI Mobile services to enhance customers' perceptions of usefulness and ease of use, thereby increasing the application's appeal.